Implementation of a Raw Material Inventory Control Information System Using the Continuous Review System Method at Naf’a Bakery - Tanhella Zein Vitadiar; I Gusti Lanang Putra Eka Prismana; Ginanjar Setyo Permadi (Jurnal Sistem Informasi Bisnis, 2025)
Effective inventory management is crucial in manufacturing industries to ensure smooth production and minimize operational costs. This study aims to design and implement an inventory control system based on the Continuous Review System (CRS) method at Naf’a Bakery, a small business located in Desa Canggu, Kediri. The implementation of CRS is expected to optimize raw material inventory, reduce storage costs, and avoid the risks of stockouts or overstocks. The methods used include observation, interviews, and demand data analysis to calculate the reorder point (ROP), optimal order quantity (EOQ), and safety stock. The results show that the implementation of CRS can reduce storage costs by approximately 30% and ordering costs by about 25%, while improving operational efficiency compared to the previous manual system. The CRS-based information system allows Naf’a Bakery to monitor inventory in real-time, ensuring that raw materials are always available at optimal levels and providing flexibility to adapt to demand fluctuations. Thus, this system not only enhances inventory management accuracy but also reduces waste and improves profitability. This study provides significant contributions to the development of more efficient inventory control systems for small and medium enterprises.